Оптимальне проектування композитних бандажів для ремонту трубопроводів - Львов, Іван Геннадійович (НТУ "ХПІ", 2017)
Представлена методологія оптимізації композиційних систем ремонту трубопроводів з об'ємними поверхневими дефектами. Через великий розмір задачі, що вирішується, ця методика розроблена з використанням методу експериментального проектування та техніки поверхонь відгуку. Для доведення ефективності пошкодженої ділянки до рівня непошкодженого трубопроводу в даному дослідженні формулюється та вирішується задача оптимізації, що базуються на еквівалентній міцності. Особливості, переваги та обмеження підходу обговорюються в їх застосуванні для оптимального проектування композитних систем ремонту трубопроводів.

Optimization methodology for composite repair systems of transmission pipelines with volumetric surface defects is presented. The inner diameter of the bandage is taken equal to the outer diameter of the pipeline and varying parameters are the thickness and length of the bandage. Due to large dimension of the numerical tasks to be solved, this methodology is developed employing the method of experimental design and response surface technique. To bring an efficiency of damaged section up to the level of undamaged pipeline, an optimization problem based on equivalent resistant (equiresistant) design is formulated and solved in the present study. Experimental design is generated by the minimal square distance Latin Hypercube sampling method, while the optimization problem was solved using random search method. To perform analysis of the stress state of the pipeline-bandage system the finite element method implemented in software ANSYS is used. Objective function values were obtained for every sample number and the objective function was approximated with second order polynomial. Obtained results showed that bandage length parameter did not have significant effect on the stress intensity values. Features, advantages and limitations of this approach are discussed in its applicability for the optimal design of composite repair systems of transmission pipelines.
Optimal design of composite repair systems of transmission pipelines
Keywords: об'ємні дефекти поверхні; міцність трубопроводу; композитный ремонт; оптимизация; volumetric surface defect; composite repair; optimisation